2017
DOI: 10.1080/1028415x.2017.1290932
|View full text |Cite
|
Sign up to set email alerts
|

Pre-conceptual and prenatal supplementary folic acid and multivitamin intake, behavioral problems, and hyperkinetic disorders: A study based on the Danish National Birth Cohort (DNBC)

Abstract: OBJECTIVE: To evaluate whether early folic acid or multivitamin supplementation during pregnancy prevents diagnosis of hyperkinetic disorders (HKD), treatment for attention deficit hyperactivity disorder (ADHD) and ADHD-like behaviors reported by parents participating in the DNBC for children at age 7. METHODS: HKD diagnosis and ADHD medication use data was obtained from the Danish National Hospital, Central Psychiatric and Pharmaceutical registers. We estimated hazard ratios (HRs) for HKD diagnosis and ADHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Three studies examined maternal folic acid supplementation in relation to offspring ADHD risk or symptoms [63,64,65,66,67], with most reporting null findings. Specifically, maternal folic acid-specific supplementation before and in early pregnancy was not associated with clinical diagnosis of hyperkinetic disorders or ADHD medication use in a large study of 35,059 children in the DNBC [65], although it was associated with a lower risk of hyperactivity-inattention problems as measured by the Strength and Difficulties Questionnaire (SDQ) among a subgroup of children followed to age seven. Similarly, maternal intake of any folic acid supplementation before or in early pregnancy was not associated with the risk of the hyperactivity-inattention problem among 6247 children in the Growing Up in New Zealand Study [63] and 420 children in the Menorca cohort in Spain [66].…”
Section: Results and Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies examined maternal folic acid supplementation in relation to offspring ADHD risk or symptoms [63,64,65,66,67], with most reporting null findings. Specifically, maternal folic acid-specific supplementation before and in early pregnancy was not associated with clinical diagnosis of hyperkinetic disorders or ADHD medication use in a large study of 35,059 children in the DNBC [65], although it was associated with a lower risk of hyperactivity-inattention problems as measured by the Strength and Difficulties Questionnaire (SDQ) among a subgroup of children followed to age seven. Similarly, maternal intake of any folic acid supplementation before or in early pregnancy was not associated with the risk of the hyperactivity-inattention problem among 6247 children in the Growing Up in New Zealand Study [63] and 420 children in the Menorca cohort in Spain [66].…”
Section: Results and Commentarymentioning
confidence: 99%
“…Among the studies previously mentioned, three also assessed the association between maternal multivitamin intake and child ADHD risk [63,65,66]. Overall, the findings are inconsistent.…”
Section: Results and Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the finding of hyperactivity/increased locomotion in powdered-chow exposed offspring, human studies evaluating the impact of vitamin and micronutrient deficiencies on offspring attention deficit hyperactivity disorder (ADHD) risk have reported mixed results (Li et al, 2019). For example, maternal multivitamin and folate intake were associated with a lower risk of ADHD diagnosis and medication use in the Danish National Birth Cohort, but not in a New Zealand birth cohort (Virk et al, 2018;D'Souza et al, 2019). Deficiencies in B vitamins and Vitamin D have also been linked to increased ADHD risk in children (Morales et al, 2015;Altun et al, 2018;Fasihpour et al, 2019;Kotsi et al, 2019), although some studies have failed to find these associations (Gustafsson et al, 2015).…”
Section: Contextualizing Adult Offspring Neurobehavioral Testingmentioning
confidence: 99%
“…While there is limited evidence for the association between maternal diet and beneficial outcomes for offspring, the observational study, KOMCHS in Japan showed that behavioural problems in childhood were less likely in children whose mothers consumed a diet high in vegetables, fruit and vitamin C during pregnancy [ 60 ] and used supplements of folate, vitamin B2 and vitamin B6 [ 61 ]. A Danish cohort study (DNBC) reported the risk for hyperkinetic disorders and treatment for ADHD to be lower in children whose mothers used multivitamins early in pregnancy compared to those who consumed folic acid only [ 62 ]. There have been limited studies to date examining the impact of diet and dietary supplementation on infants whose mothers experienced mental health difficulties during the antenatal period.…”
Section: Introductionmentioning
confidence: 99%